2020
DOI: 10.1007/s10499-020-00581-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new strain of lymphocystis disease virus (LCDV) in captive-bred clownfish Amphiprion percula in South Sulawesi, Indonesia

Abstract: Breeding of ornamental marine fishes was initiated in Makassar, South Sulawesi, Indonesia, to protect reef ecosystems from destructive fishing and to supplement income of local communities. However, stress associated with captive breeding conditions could enhance vulnerability of fish to disease. Wild-and captive-bred clownfish Amphiprion percula showed clinical signs such as white spots and warts typically associated with lymphocystis disease. Sequencing a portion of the DNA polymerase gene confirmed the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…The fully developed warts on the body surface were present in the caudal peduncle and abdomen (Figure 1). This clinical sign was similar to the white wart on the dorsal fins of LCDV-infected clownfish A. percula in Makassar (Lam et al, 2020). In this study, the lesions in the mouth were found in one fish (data not shown).…”
Section: Clinical Signssupporting
confidence: 78%
See 2 more Smart Citations
“…The fully developed warts on the body surface were present in the caudal peduncle and abdomen (Figure 1). This clinical sign was similar to the white wart on the dorsal fins of LCDV-infected clownfish A. percula in Makassar (Lam et al, 2020). In this study, the lesions in the mouth were found in one fish (data not shown).…”
Section: Clinical Signssupporting
confidence: 78%
“…Lymphocystis disease virus (LCDV) is the causative agent of lymphocystis disease, affecting more than 140 species of marine and freshwater fish worldwide, both wild and farmed fish. The pathognomonic signs of lymphocystis-infected fish are mostly external multinodular tumor-like or wart-like masses growths on the fins, skin, or gills (Hick et al, 2016;Lam et al, 2020). Nodular lesions may also be observed on the surfaces of viscera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocystis disease virus (LCDV), a member of the genus lymphocystivirus within the Iridoviridae family [ 1 , 2 ], is the etiological agent of lymphocystis disease. Lymphocystis disease is a well-known disease that is characterized by the presence of pearl-like nodules on the skin, fins and internal organs of the fish [ 3 ], which has affected more than 140 marine, brackish and freshwater fish worldwide [ 4 ], and new LCDV isolations are still continuously found in wild and cultured fish species [ 5 , 6 , 7 ]. The incidence rate of this disease may reach 70%, causing significant economic losses for the aquaculture industry [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anemonefish are among the most commonly captivebred ornamental marine fish (Pouil et al, 2020). Successful anemonefish mariculture occurs commercially in countries including Indonesia (Sinansari & Priono, 2019;Lam et al, 2020), indicating a shift from wild harvest to mariculture. Ideally, both the anemones and anemonefish should be sustainably captive bred for the marine aquarium trade.…”
Section: Opportunities For Mariculture and Conservationmentioning
confidence: 99%